Flavonoids from the Leaves of Melastoma malabathricum L. - D, Susanti,; H.M, Sirat; F, Ahmad; N, Aimi; M, Kitajima, (Malaysian Journal of Science, 2005)
Chemical studies on the leaves of Melastoma malabathricum with white petals (senduduk putih) have been carried out. Purification of the methanolic extract by chromatographic methods afforded quercetin 1 and quercitrin 2.